Objective assessment of antianginal treatment: a double-blind comparison of propranolol, nifedipine, and their combination. Issue 6234 (19th July 1980) - Lynch, P; Dargie, H; Krikler, S; Krikler, D
Abstract : In a double-blind clinical trial the antianginal effects of nifedipine (30 and 60 mg/day) and propranolol 240 and 480 mg/day) and a combination of both drugs were compared with those of placebo in 16 patients with severe exertional angina pectoris. Response to treatment was assessed by the objective criteria of 16-point precordial exercise mapping and 48-hour ambulatory electrocardiographic monitoring and subjectively by analysis of patients' daily diaries of episodes of angina and consumption of glyceryl trintrate. The incidence of pain and consumption of glyceryl trinitrate were significantly decreased by each drug compared with placebo, and the combination produced a further significant improvement. Objectively the total area and amount of ST depression on the precordial exercise map and the total number of episodes of ST depression detected on ambulatory monitoring confirmed the efficacy of each treatment regimen; the combination was significantly better than either drug alone (p <0.005). The objective methods permitted greater separation of treatment efficacy and showed reliably that the combination of propranolol and nifedipine was significantly better than either drug alone. Thus this combination is a safe and effective form of treatment for angina.